ChemInform Abstract: [Cs6Cl][Fe24Se26]: A Host‐Guest Compound with Unique Fe—Se Topology. Issue 24 (27th May 2016) - Valldor, Martin; et al.,
Abstract: Polycrystalline Se‐substituted bartonite [Cs6 Cl][Fe24 Se26 ] is obtained by annealing stoichiometric amounts of Cs2 Se, CsCl, Fe, and Se (Al2 O3 crucible in evacuated silica tubes, 500 °C, 60 h).